The Dialectics of Health and Disease in the Magic Mountain - Dr. Barnali Sikder (International Journal of Social Science and Human Research, 2026)
This article aims to concentrate on the dialectics of health and disease in Thomas Mann’s The Magic Mountain. It will be a concentrated reading of Mann’s novel to argue that the dialectics of health and disease work to bring out the culmination of thought. In this peak mystical state, transformation is innate, which can bridge negotiations and collapse boundaries. Within this world of negotiations and collapsing boundaries Mann has seen a connection between art and disease. This relation between art and disease is going to be analysed in this article to understand Mann’s take on the dialectics of disease and health.